Alternative for the regionalization of flow duration curves. Issue 3 (3rd July 2019) - Silva, Raimunda da Silva e; Blanco, Claudio José Cavalcante; Pessoa, Francisco Carlos Lira
Abstract : The objective of the present work is to produce a regionalization model of flow duration curves, proposing the grouping of watersheds as a function of the drainage area without the use of cluster analysis techniques. Curves were fitted with 5 mathematical regression models: power, exponential, logarithmic, quadratic and cubic. The regionalization model was established by multiple regression. The spatial variation of the parameters of models was caused by drainage area, annual mean rainfall, length and head of the main river. The model was validated by the jack-knife procedure and the best fitting of the cubic model was represented by mean squared errors ( e %) and Nash-Sutcliffe coefficients (Nash). The results show a good fitting of the cubic model to the observed flow duration curves; and a good simulation of the curves by the regional model tested in the validation, with the exception of a few streamflow gauges.